GENERAL PRINCIPLES OF CREATING TERMINOLOGICAL DICTIONARIES - Ergashev Muhammadjon Raxmonovich (Galaxy International Interdisciplinary Research Journal, 2022)
Learning a foreign language is not an easy matter, so creating dictionaries is vitally important. The purpose of the article is to research for some principals of creating terminological dictionaries and its importance.